Whither Gender Studies in Sarawak? - Hew, Cheng Sim (Springer Singapore, 2017)
This chapter reviews gender research in the field of sociology and anthropology in Sarawak. The discussion is contextualised in the wider debates of women and gender studies and explores the development of anthropology of women to a feminist anthropology and a feminist ethnography. The chapter argues three salient points. First, research that disaggregates women and men and discusses their differential experience of a social phenomenon is not necessarily a gender study because, for the purposes of this chapter, gender studies is defined as research with an explicit feminist agenda. Second, anthropologists studying indigenous societies in Sarawak often point out that gender is unmarked and therefore gender relations are of little interest. I argue instead that gender is deeply implicated in processes of social transformation and the black box of gender relations requires unpacking in the context of rapidly changing Sarawak. Third, the future of gender studies in Sarawak in the field of anthropology and sociology is challenging, as there is no critical mass of researchers and academics in this specific field for capacity building among students and young scholars.